2023
DOI: 10.3390/ijms24087403
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Attenuates the Mitochondrial RNA-Mediated Cellular Response to Immunogenic Stress

Abstract: Human mitochondria contain a circular genome that encodes 13 subunits of the oxidative phosphorylation system. In addition to their role as powerhouses of the cells, mitochondria are also involved in innate immunity as the mitochondrial genome generates long double-stranded RNAs (dsRNAs) that can activate the dsRNA-sensing pattern recognition receptors. Recent evidence shows that these mitochondrial dsRNAs (mt-dsRNAs) are closely associated with the pathogenesis of human diseases that accompany inflammation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Direct suppression of mt-dsRNAs reversed the glandular phenotypes of SS [121]. The same group also demonstrated the therapeutic efficacy of muscarinic receptor ligand acetylcholine and resveratrol in reversing the activated response to immunogenic stressors in salivary gland acinar cells [122]. Xu et al confirmed that lactate levels were significantly upregulated in the salivary glands of patients with SS and lactate triggered an inflammatory response by damaging mtDNA and causing mtDNA leakage in glandular epithelial cells.…”
Section: Sjögren's Syndromementioning
confidence: 95%
“…Direct suppression of mt-dsRNAs reversed the glandular phenotypes of SS [121]. The same group also demonstrated the therapeutic efficacy of muscarinic receptor ligand acetylcholine and resveratrol in reversing the activated response to immunogenic stressors in salivary gland acinar cells [122]. Xu et al confirmed that lactate levels were significantly upregulated in the salivary glands of patients with SS and lactate triggered an inflammatory response by damaging mtDNA and causing mtDNA leakage in glandular epithelial cells.…”
Section: Sjögren's Syndromementioning
confidence: 95%
“…However, it remains unclear whether mtRNAs are always induced downstream of antiviral response or by other stressors. For example, mtRNAs were not induced under endoplasmic reticulum stress from increased misfolded proteins (Yoon et al 2023). Thus, we began our investigation by specifying stressors that can potentially modulate mtRNA expression.…”
Section: Mtrna Expression Is Upregulated During Antiviral Signalingmentioning
confidence: 99%
“…mt-dsRNAs are generated due to bidirectional transcription of the mitochondrial circular genome 24,25 , which produces long complementary RNAs denoted as heavy and light strand RNAs 20,2631 . Under stress conditions, mt-dsRNAs are released to the cytosol through BCL-2-associated X protein (BAX)/BCL-2- homologous antagonist/killer (BAK1) channel 28,32,33 where they activate MDA5 and PKR to initiate IFN response and apoptosis 28,3436 . To limit mt-dsRNA expression, light strand mtRNAs are quickly degraded by mtRNA degradosome complex consisting of human suppressor of var1,3-like (hSUV3) 37 and polyribonucleotide nucleotidyltransferase 1 (PNPT1) 3840 .…”
Section: Introductionmentioning
confidence: 99%